2013
DOI: 10.1111/1574-6968.12353
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the effects of silver phosphate and selenium nanoparticles onStaphylococcus aureusgrowth reveals potential for selenium particles to prevent infection

Abstract: Interactions of silver phosphate nanoparticles (SPNPs) and selenium nanoparticles (SeNPs) with Staphylococcus aureus cultures have been studied at the cellular, molecular and protein level. Significant antibacterial effects of both SPNPs and SeNPs on S. aureus were observed. At a concentration of 300 μM, SPNPs caused 37.5% inhibition of bacterial growth and SeNPs totally inhibited bacterial growth. As these effects might have been performed due to the interactions of nanoparticles with DNA and proteins, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 19 publications
2
67
0
1
Order By: Relevance
“…Despite this variable antimicrobial efficacy of untreated SeNPs towards the different bacterial strains tested, as a general rule MIC values increased with the progressive denaturation of the organic coating layer. These findings suggest that antimicrobial activity of SeNPs is size‐dependent, with higher inhibiting effects associated with the smallest ones, as already reported in previous studies (Lu et al ., 2013; Chudobova et al ., 2014; Zonaro et al ., 2015). Indeed, denaturation of the external organic cap which leads to a progressive increase in particle dimensions coincides with a gradual drop in antibacterial efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this variable antimicrobial efficacy of untreated SeNPs towards the different bacterial strains tested, as a general rule MIC values increased with the progressive denaturation of the organic coating layer. These findings suggest that antimicrobial activity of SeNPs is size‐dependent, with higher inhibiting effects associated with the smallest ones, as already reported in previous studies (Lu et al ., 2013; Chudobova et al ., 2014; Zonaro et al ., 2015). Indeed, denaturation of the external organic cap which leads to a progressive increase in particle dimensions coincides with a gradual drop in antibacterial efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of biological properties, the effect of UV radiation (laboratory and stratospheric) on the resistance of bacterial strains to environmental externalities, such as conventional antibiotic drugs or their alternative as selenium nanoparticles [24,25], was further monitored. It was shown that the exposure of UV significantly weakened the resistance of bacteria, and the application of antibiotic drugs or nanoparticles became more effective.…”
Section: Resistancementioning
confidence: 99%
“…Even low concentrations of silver are very effective as a germicidal agent. The antimicrobial effect of silver ions or AgNPs was confirmed by several studies (Chudobova et al, 2013a(Chudobova et al, , b, 2014a.…”
Section: Silver Nanoparticlesmentioning
confidence: 70%
“…Long-term exposure of AgNPs larger than 20 nm to eukaryotic cells may affect them negatively. A combination of AgNPs with a biopolymer like chitosan is a possible solution for its eukaryotic or prokaryotic toxicity (Chudobova et al, 2013b).…”
Section: Silver Nanoparticlesmentioning
confidence: 99%